2010
DOI: 10.4056/sigs.43526
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of the Medicago microsymbiont Ensifer (Sinorhizobium) medicae strain WSM419

Abstract: Ensifer (Sinorhizobium) medicae is an effective nitrogen fixing microsymbiont of a diverse range of annual Medicago (medic) species. Strain WSM419 is an aerobic, motile, non-spore forming, Gram-negative rod isolated from a M. murex root nodule collected in Sardinia, Italy in 1981. WSM419 was manufactured commercially in Australia as an inoculant for annual medics during 1985 to 1993 due to its nitrogen fixation, saprophytic competence and acid tolerance properties. Here we describe the basic features of this o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
82
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 40 publications
6
82
1
4
Order By: Relevance
“…T was found to be more closely related to Methylobacterium nodulans (Alphaproteobacteria) based on its DNA and amino acid sequences, but its nifH sequence is closer to free-living Burkholderia (Betaproteobacteria) (Figure 3) [6,7,63]. As stated earlier, in contrast to STM678 T , which nodulates papilionoideae, in our complete genome study we found that B. tuberum sv.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…T was found to be more closely related to Methylobacterium nodulans (Alphaproteobacteria) based on its DNA and amino acid sequences, but its nifH sequence is closer to free-living Burkholderia (Betaproteobacteria) (Figure 3) [6,7,63]. As stated earlier, in contrast to STM678 T , which nodulates papilionoideae, in our complete genome study we found that B. tuberum sv.…”
Section: Discussioncontrasting
confidence: 47%
“…The analysis showed that the nifH and nodA sequences of another B. tuberum strain (CCGE1002), which was isolated from Mimosa occidentalis in Mexico, and which belongs to the mimosae symbiovar of B. tuberum, were grouped within clades of Beta-rhizobial genes. Indeed, [63] that the nodA aa sequence of CCGE1002 clustered with Beta-rhizobial genes, which is consistent with relationships deduced using nodIJ sequences. However, the partial sequences are inaccurate in some aspects, and in the present study, we have found that there is little interaction between the two rhizobial clades, and we further suggest that the nod genes of Alpha-and (Mimosa-nodulating) Beta-rhizobia evolved independently, but we also lend support to the concept that lateral gene transfer has occurred in some clusters.…”
supporting
confidence: 67%
See 3 more Smart Citations